PENDIDIKAN BERBASIS TEKNOLOGI (PERMASALAHAN DAN TANTANGAN) - Khotimah, Husnul; Astuti, Eka Yuli; Apriani, Desi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Educational technology is designed to help solve educational problems, so as to be able to provide benefits in an effort to improve the quality of learning. Various forms of learning experiences, both those that can be achieved in the classroom and outside the classroom and learning messages, can be packaged by taking into account the principles and principles of educational technology. With the use of learning technology it is expected that educational messages can be packaged more systemically-systematically in both physical and virtual packaging, which is no longer limited by the dimensions of space or time, so that students can be accepted well, easily, and extensively, and create pleasant education. flexible in the dimensions of time, space, and developing the potential of students individually. In addition to providing benefits, technology in the field of education also presents several obstacles that have a positive impact on education.